2019
DOI: 10.2196/15323
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an App for Day-to-Day Postoperative Care Education on Patients With Total Knee Replacement: Randomized Controlled Trial

Abstract: Background Patients who undergo primary Total Knee Replacement surgery (TKR) are often discharged within 1-3 days after surgery. With this relatively short length of hospital stay, a patient’s self-management is a crucial factor in optimizing the outcome of their treatment. In the case of TKR, self-management primarily involves adequate pain management, followed by physiotherapy exercises and daily self-care activities. Patients are educated on all these topics by hospital staff upon discharge from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 33 publications
4
131
0
2
Order By: Relevance
“…Of the 33 included studies, 8 officially reported authors’ conflicts of interest, stating that they held shares in the app. Furthermore, several of the study groups were provided with the apps free of charge [ 28 ], which has clear implications on the usability domain of satisfaction; users who have paid for an app might be expected to have higher expectations than those who have been given an app for free. Perhaps more worryingly, a number of groups [ 38 ] declared no conflict of interest, despite seemingly being founders of their app.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 33 included studies, 8 officially reported authors’ conflicts of interest, stating that they held shares in the app. Furthermore, several of the study groups were provided with the apps free of charge [ 28 ], which has clear implications on the usability domain of satisfaction; users who have paid for an app might be expected to have higher expectations than those who have been given an app for free. Perhaps more worryingly, a number of groups [ 38 ] declared no conflict of interest, despite seemingly being founders of their app.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3 , function was significantly improved by perioperative interventions in 18 studies. Pain coping skills training [ 62 ], audiorecording guided imagery scripts [ 61 ], video promoting self-confidence and psychological support [ 64 ], music [ 35 , 36 ], occupational therapy in combination with self-monitoring using a diary [ 68 ], various types of education [ 41 , 43 , 45 , 47 , 51 53 ], weight-bearing biofeedback training [ 67 ], and psychological therapies (behavioural change intervention [ 60 ] and cognitive behavioural therapy [ 57 – 59 ]) positively affected any, but not all, of the functional outcome measures after TKA. In the most recent study by Riddle et al [ 63 ], patients receiving pain coping skills training did not have significantly better scores on WOMAC function and the short physical performance battery.…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies with patients receiving TKA were included by Bay et al [ 25 ]. Compared to that review, we included fifteen additional RCTs [ 33 , 34 , 37 , 38 , 41 , 44 , 45 , 49 , 53 , 54 , 56 58 , 58 , 63 ]. Second, due to the current lack of RCTs on one specific type of intervention focused on psychological distress (for example only pain coping skills training) applied to patients undergoing TKA, we have decided to also include a wider range of study designs to create a complete overview of the perioperative interventions focused on psychological distress that have been used to decrease pain and improve function and/or QoL after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the importance of efficient use of hospital resources and the cuts of hospitalization costs, m/eHealth programs can support and guide patients during the recovery period at home. With m/eHealth programs, efficient use of hospital resources can be maintained and the needs of the patients can be fulfilled [ 19 , 20 , 21 , 22 , 23 ]. However, before such an m/eHealth program can be developed, consensus among different healthcare professionals about recommendations for return to daily life activities needs to be reached.…”
Section: Introductionmentioning
confidence: 99%